Loss of CDKN2A at chromosome 9 has a poor clinical prognosis and promotes lung cancer progression - Wei Liu; Congwen Zhuang; Tengfei Huang; Shengsheng Yang; Meiqing Zhang; Baoquan Lin; Yi Jiang (Molecular Genetics & Genomic Medicine, 2020)
Abstract Objective This study aimed to identify critical genes involved in the tumor biology of lung cancer via datamining of The Cancer Genome Atlas (TCGA) with special focus on gene copy number variation. Methods Genomic deletion and amplification were analyzed with cBioportal online tools. Relative expression of Cyclin Dependent Kinase Inhibitor 2A (CDKN2A) was analyzed by both real‐time polymerase chain reaction (PCR) and Western blot. The abundance of methylthioadenosine phosphorylase (MTAP) and epithelial‐mesenchymal transition markers were analyzed by real‐time PCR. Cell proliferation was determined by cell counting kit‐8 method and cell viability was measured with 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide assay. The cell migration and invasion were measured with transwell chamber assay, and migrative capacity was further evaluated by wound healing assay. Results We found the frequent loss of CDKN2A was associated with its downregulation in lung cancer, and siRNA‐mediated CDNKN2A knockdown significantly stimulated cell proliferation, invasion, and migration. Mechanistically, we unraveled that MTAP, which was positively correlated with CDKN2A, predominantly mediated the antitumoral function of CDKN2A in lung cancer. Conclusion Our study consolidated the involvement of CDKN2A‐MTAP signaling in the context of lung cancer.